Antibody drug conjugates in non-small cell lung cancer: An emerging therapeutic approach. (January 2022) - Marks, S; Naidoo, J
Abstract: The current standard-of-care for the treatment of advanced non-small cell lung cancer (NSCLC) incorporates targeted therapies, immune-checkpoint inhibitors (ICI) and systemic chemotherapy. Antibody-drug conjugates (ADC) are a class of anti-cancer therapy capable of transporting cytotoxic drugs directly to tumour cells, thus harnessing the strengths of both cytotoxic chemotherapy and targeted therapy. In this review we provide a comprehensive review the design, mode of action, and mechanisms of resistance to ADCs in NSCLC. We also summarize the clinical development of several promising ADCs in early phase clinical trials for the treatment NSCLC. including ADCs against well-established targets (e.g.HER2 in breast cancer, Nectin4 in urothelial cancer), novel antigenic targets (e.g. HER3, TROP2, PTK7, CEACAM5), as well as promising combinations with agents known to be active in NSCLC such as tyrosine kinase inhibitors and ICI therapy, as a strategy to overcome mechanisms of resistance to ADC therapy.